1998
DOI: 10.1111/j.1559-1816.1998.tb01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing Behavioral Findings Across Times, Samples, and Measures: A Study of Condom Use1

Abstract: Data from a Knowledge, Attitude, Belief, and Practices (KABP) Survey, administered to a sample of residents of Saint Vincent and the Grenadines, were used to replicate a previous study (Fishbein, Trafimow, Francis, et al., 1995) that investigated the relative importance, as predictors of condom use, of selected theoretical variables from the theory of reasoned action (Fishbein & Ajzen, 1975), and the theory of planned behavior (Ajzen & Madden, 1986). Besides addressing generalization problems, the study tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…As Fishbein and his colleagues (Fishbein et al, 1992(Fishbein et al, , 1993(Fishbein et al, , 1995; see also Albarracín, Fishbein, & Middlestadt, 1998) observed, all of these theories suggest a number of different intervention strategies that can be expected to change behavior. Each strategy dictates the particular types of content of an intervention and the ways in which the intervention affects behavior.…”
Section: Theoretical Assumptions Intervention Strategies and Mediatmentioning
confidence: 99%
“…As Fishbein and his colleagues (Fishbein et al, 1992(Fishbein et al, , 1993(Fishbein et al, , 1995; see also Albarracín, Fishbein, & Middlestadt, 1998) observed, all of these theories suggest a number of different intervention strategies that can be expected to change behavior. Each strategy dictates the particular types of content of an intervention and the ways in which the intervention affects behavior.…”
Section: Theoretical Assumptions Intervention Strategies and Mediatmentioning
confidence: 99%
“…While various theories propose slightly different underlying cognitive structures, an integrated behavioural model illustrated by Fishbein (2000) includes those factors generally accepted as influencing condom use (Albarracin et al, 1998(Albarracin et al, , 2001(Albarracin et al, , 2004Crepaz & Marks, 2002;Terry, 1993). This model holds that three cognitive factors: condom-use attitudes, normative beliefs and selfefficacy, indirectly influence condom-use behaviour through the intention to use condoms.…”
Section: Introductionmentioning
confidence: 99%
“…Measures should specify the behavior, object of the behavior, time and behavioral context. To predict a patient's intention to use clonidine for heroin detoxification, for example, an investigation should assess the attitude toward taking clonidine (behavior) for heroin detoxification (context).The Theory of Reasoned Action and the Theory of Planned Behavior have found widespread application to health-related behaviors including HIV risk reduction and use of contraceptives (Albarracin, Fishbein, & Middlestadt, 1998;Fishbein & Guinan, 1996;McCarty, 1981), and (Bearden & Woodside, 1978;McCarty, Morrison, & Mills, 1983;Schlegel, Crawford, & Sanborn, 1977;Schlegel, D'Avernas, Zanna, DeCourville, & Manske, 1992). Reviews of applications of the model to health behaviors report that the model can explain 40 to 50 percent of the variation in intention (Godin & Kok, 1996;Sutton, 1998).…”
mentioning
confidence: 99%